The mediating effect of students’ attitude to student career aspiration and mathematics achievement - Quiliano Jr Gonzales Oracion; Ivy Lyt Sumugat Abina (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2021)
Mathematics low achievement has undeniably been found in both national examinations and international assessments. An educator needs to be aware and determine the factors in students’ achievement. However, there were no observable studies focusing on the mediating effect of students' attitudes toward career aspiration and academic achievement. With this, it aims to determine the mediating effect of students’ attitudes on students’ career aspirations and academic achievement in learning Mathematics in a higher educational institution in the Davao Region.  The researcher utilized sets of adopted and self-made test questionnaires to gather data from the 199 respondents.  In analyzing the data, the researcher performed descriptive statistics, Pearson Product Moment Correlation Coefficient, and Regression Analysis as statistical tools. These analyses indicated that students have a high level of career aspiration, a satisfactory level of academic achievement, an average level of attitude towards mathematics, and an insignificant relationship between students’ career aspirations and academic achievement. The relationship between the student’s attitude and career aspiration is significant. The latter is the only relationship that is significant among all steps, and thus full and partial mediation analysis will not be warranted. Based on the findings, the students must be responsible for helping themselves to make an efficient move in developing their aspiration to have a considerable positive attitude in learning mathematics.